Prophylactic Kinesio taping enhances balance for healthy collegiate players - Chang, H.-Y.; Huang, Y-H.; Cheng, S.-C.; Yeh, C.-Y.; Wang, C.-H. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study was to investigate the effects of prophylactic Kinesio taping and athletic taping on the functional performance of the lower extremities in healthy collegiate players with tapes applied to the dominant leg. METHODS: The study design was a prospective, randomized, clinical trial with comparison of groups. The 32 healthy collegiate players who participated in this study were randomly assigned to 2 groups, an athletic taping group and a Kinesio taping group. Active range of motion of ankle joint, ankle plantar-flexor strength, endurance, vertical jump performance, and dynamic balance were used to measure the player`s functional performance of the lower extremities. These tests were conducted 2 times at 4-hour intervals before and after different tapes were applied. The repeated measures analysis of variance was used to examine the interaction in functional performance between the groups before and after the tapes applied. RESULTS: The results found less limitation of range of motion in active ankle dorsiflexion and significant improvement in dynamic balance in the Kinesio taping group (F=5.150, P=0.031, F=18.766, P<0.001, respectively) compared with the athletic taping group. CONCLUSIONS: The prophylactic Kinesio taping could enhance dynamic balance and result in less restriction of range of motion of ankle dorsiflexion in healthy collegiate players.